THE PHENOMENON OF ALLUSION IN LINGUISTICS AND ITS LINGUOPOETHIC CHARACTERISTICS (Universal International Scientific Journal, 2026)
This article discusses the essence, theoretical foundations and functional significance of the phenomenon of allusion in the framework of linguistics and linguopoetics. Allusion is analyzed as an intertextual unit, revealing its semantic, pragmatic and stylistic features. Also, the aesthetic and communicative functions of this phenomenon are shown through examples of the use of allusion in Uzbek artistic speech.
Keywords: allusion; intertextuality